Inovasi Kebijakan Pemerintah Daerah Dalam Menurunkan Angka Kemiskinan Di Kabupaten Nias Barat - Halawa, Abdi Gunawan; Pasaribu, Johnson; Tobing, Artha Lumban (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
Poverty is a complex problem faced almost throughout the world, including Indonesia. West Nias Regency has a high poverty rate compared to other areas in North Sumatra, although the trend has shown a decline since 2015. This study aims to analyze innovations in local government policies in reducing poverty rates in West Nias Regency. With a qualitative-descriptive approach, this research explores policies in various sectors such as education, health, infrastructure, and community economic empowerment. The research results show that policy innovation based on inter-sector integration and an approach oriented towards local wisdom contribute to reducing poverty rates. However, challenges such as limited infrastructure, accessibility, and program sustainability still need to be addressed. Strategic recommendations are proposed to improve the effectiveness of policies in poverty alleviation in West Nias Regency.